One more river to cross - Kirkpatrick, Jane, 1946- (Revell, a division of Baker Publishing Group, 2019)
Based on true events, this compelling survival story by award-winning novelist Jane Kirkpatrick is full of grit and endurance. Beset by storms, bad timing, and desperate decisions, 8 women, 17 children, and one man must outlast winter in the middle of the Sierra Nevada Mountains in 1844.